2021
DOI: 10.1038/s41598-021-98817-9
|View full text |Cite
|
Sign up to set email alerts
|

Refractive lens power and lens thickness in children (6–16 years old)

Abstract: To examine the refractive lens power (RLP) and lens thickness and their associated factors in children from North-Western China. Children from two schools (primary school and junior high school) in the North-Western Chinese province of Qinghai underwent a comprehensive ophthalmic examination including biometry and cycloplegic refractometry. The RLP was calculated using Bennett’s equation. The study included 596 (77.9%) individuals (mean age: 11.0 ± 2.8 years; range: 6–16 years) with a mean axial length of 23.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The LT change could better reflect morphological changes in the lens but has been less studied. In a cross-sectional study including 596 children from Qinghai, China, Lu et al 11 reported that LP decreased from 6 to 13 years of age followed by a slight increase from 13 to 16 years of age. Hashemi et al 18 included 6624 Iranian children in their study and found decreasing LP from 6 to 12 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LT change could better reflect morphological changes in the lens but has been less studied. In a cross-sectional study including 596 children from Qinghai, China, Lu et al 11 reported that LP decreased from 6 to 13 years of age followed by a slight increase from 13 to 16 years of age. Hashemi et al 18 included 6624 Iranian children in their study and found decreasing LP from 6 to 12 years of age.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 However, the role of the lens and its interplay with AL changes during myopia development has not been investigated sufficiently. Several previous studies demonstrated decreasing lens thickness (LT) and lens power (LP) with age in childhood, 5 , 11 – 13 but there is insufficient detailed longitudinal data to provide an overall picture of how the lens changes from preschool years to adolescence, 14 16 and it is unclear whether the lens is actively modulated in relation to axial elongation during the onset of myopia, 15 …”
mentioning
confidence: 99%
“…Previous studies have demonstrated a negative correlation between LP and age, and decreasing compensatory ability of LP with increasing age. [28][29][30][31][32] In school children, the anterior and posterior curvatures of the lens flatten as the lens become thinner, which consequently leads to a decline in surface power of the lens. Additionally, a steeper gradient index with compaction of the lens nucleus results in the loss of internal power within the lens.…”
Section: Discussionmentioning
confidence: 99%
“…IOLMaster 700 biometry showed that the axial length was 22.07 mm in the right eye and 22.01 mm left eye ( Table 1 ), which were within mean ± 1.96 standard deviation (SD) of the normal reference range ( 14 20 ). While the lens thickness (right 4.38 mm, left 4.31 mm) was significantly greater than normal ( Table 1 ) ( 16 18 , 21 , 22 ). PENTACAM illustrated visually that the lens of the proband was thicker than normal children (control) of the same age ( Figure 1B , red line).…”
Section: Introductionmentioning
confidence: 84%